Analysis of convergences among knowledge management maturity models and the pillars of the global innovation index - da Silva, Elaine; Damian, Ieda Pelogia Martins [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (Universidade Federal da Paraíba, 2020)
Given the importance of innovation for contemporary society, the growing studies about knowledge management and the assumption that knowledge is a fundamental element for innovation, this article aims to verify if structured knowledge management processes can influence the generation of innovation, seeking to identify convergences between the two. For that, a literature review was carried out on the themes: ‘knowledge management’ and ‘innovation’. After the analysis, a synthesis table was presented presenting the key areas of knowledge management maturity models, which allowed to highlight the basic elements of knowledge management and the most comprehensive model among the analyzed. Finally, the key areas of the selected knowledge management maturity model and the elements that constitute the fundamental pillars for the generation of innovation and described in an instrument that measures innovative activity worldwide are compared. The analysis provided evidence of convergences between the knowledge management model and innovation indicators, ratifying the hypothesis that structured knowledge management processes can significantly contribute to the generation of innovation in organizational contexts.
Análise das convergências entre os modelos de maturidade de gestão do conhecimento e os pilares do índice global de inovação
Keywords: Innovation Indicators; Knowledge Management; Maturity Models of Knowledge Management; Model KMMM; Global Innovation Index